Cristo sin Cristo: religión e idolatría desde las miradas de Edmund Husserl y Simone Weil - Orellano, Carlo (2021)
The following research has the aim to stress out the similarities and connections between Edmund Husserl’s and Simone Weil’s analysis concerning idolatry as a religious phenomenon. In order to achieve it, it will be necessary to analyse how religion could find a place inside Husserl’s phenomenological frame; after that, the main focus will lay on the interpretation of one of Weil’s posthumous works. Regard-ing the Austrian philosopher, it is important to point out the fact that a continuum between his static and genetic analyses will be implicitly accepted.